2007
DOI: 10.2353/ajpath.2007.070917
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral Malaria Pathogenesis

Abstract: Cerebral malaria (CM) attributable to Plasmodium falciparum infection is estimated to affect 575,000 children in sub-Saharan Africa every year 1 and is among the deadliest forms of malaria, with an average estimated mortality rate of 18.6%. 2 Although extensive studies have been conducted in murine models of CM and in human populations with CM, the pathogenesis of CM is still incompletely understood. Studies to date suggest that CM is attributable to a combination of local brain tissue damage from microvascula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…Cerebral malaria (CM) is the most severe manifestation of Plasmodium falciparum malaria infection with an average mortality rate of around 20% even when treated with anti-malarial drugs [1], [2]. Despite decades of study, a detailed understanding of the causative mechanisms in CM has so far not been achieved.…”
Section: Introductionmentioning
confidence: 99%
“…Cerebral malaria (CM) is the most severe manifestation of Plasmodium falciparum malaria infection with an average mortality rate of around 20% even when treated with anti-malarial drugs [1], [2]. Despite decades of study, a detailed understanding of the causative mechanisms in CM has so far not been achieved.…”
Section: Introductionmentioning
confidence: 99%
“…Microarray analyses have been performed on brain tissues from CM-susceptible (C57BL/6, CBA) and CM-resistant (BALB/c, DBA/2) mouse strains after P. berghei ANKA infection [13, 14, 52, 53, 72]. These analyses revealed that interferon (IFN) and IFN-regulating processes play a major role in experimental CM pathogenesis [13, 14, 42, 72]. Furthermore, it has been suggested that the C57BL/6 and CBA strains, which are predisposed towards Th1 immune responses, are susceptible to experimental CM, whereas BALB/c, which is predisposed toward Th2 responses, is resistant [28, 29].…”
Section: Malaria Complications In the Brainmentioning
confidence: 99%